1990
DOI: 10.1038/bjc.1990.163
|View full text |Cite
|
Sign up to set email alerts
|

Production of immunoreactive insulin-like growth factor-I (IGF-I) and IGF-I binding proteins by human lung tumours

Abstract: Summary The production of insulin-like growth factor I (IGF-I) and IGF-I binding proteins (BPs) by human lung tumour cell lines in vitro has been examined and the levels of these substances in the serum of lung cancer patients investigated. While small cell lung cancer (SCLC) cell lines secreted both IGF-I and BPs, non-small cell lung cancer (NSCLC) cell lines secreted BPs only. No evidence of increased serum IGF-I levels was obtained in a cohort of 52 lung cancer patients having SCLC and NSCLC histologies. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 27 publications
2
29
3
Order By: Relevance
“…This finding is in accordance with other reports describing elevated IGFBP-2 levels in various malignant diseases, such as prostate cancer (Kanety et al, 1993), Wilms' tumour (Zumkeller et al, 1993) and lung cancer (Reeve and Payne, 1990). Whereas the stimulation of cell proliferation by IGFs is well established (Camacho-Hubner et al, 1991;Jones and Clemmons, 1995) the functions of IGFBP-2 on tumour and normal cells are still unknown.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in accordance with other reports describing elevated IGFBP-2 levels in various malignant diseases, such as prostate cancer (Kanety et al, 1993), Wilms' tumour (Zumkeller et al, 1993) and lung cancer (Reeve and Payne, 1990). Whereas the stimulation of cell proliferation by IGFs is well established (Camacho-Hubner et al, 1991;Jones and Clemmons, 1995) the functions of IGFBP-2 on tumour and normal cells are still unknown.…”
Section: Discussionsupporting
confidence: 92%
“…As IGFBP-2 concentrations have been reported to be elevated in patients with several malignant tumors (42,43), in particular prostate carcinoma (39), one might hypothesize that the association between IGFBP-2 and functional ability is dependent on the presence of prostate malignancies. However, even within the group of individuals with elevated PSA levels, there was no relation between IGFBP-2 and PSA, or other prostate abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Macauly et al [142] measured serum IGF-I concentrations in 42 SCLC patients and concluded that IGF-I levels do not correlate with tumor bulk or with the therapeutic responsiveness of SCLC. Reeve et al [143] observed that IGFs were highly upregulated in the sera of SCLC as well as NSCLC patients and the levels of these proteins in blood correlate with course of treatment in such patients. Further studies are needed for better evaluation of these substances.…”
Section: Hormones As Cancer Biomarkersmentioning
confidence: 99%